Physical determinants of volleyball overhead serve performance: a systematic review of biomechanical correlates - Ikhwan Sukri; Alnedral Alnedral; Arsil Arsil; Yuni Astuti (Journal of Educational and Learning Studies, 2026)
Overhead serve performance in volleyball depends on a complex interaction of arm muscle strength, lower-limb power, and motor coordination, yet an integrated understanding of these contributors remains limited. This systematic literature review, conducted according to PRISMA 2020 guidelines, analyzed 50 studies retrieved from Scopus (2020–2026) following a four-stage screening process and thematic synthesis based on Thomas and Harden's three-stage coding procedure. Three themes emerged: (1) upper-limb and rotator-cuff strength consistently predicts serve and spike velocity but raises shoulder-injury risk under poorly managed training loads; (2) complex, plyometric, and small-sided power training enhances jump-serve height and arm-swing speed; and (3) coordinated trunk rotation, arm-swing sequencing, and hand-eye coordination are the primary mechanisms linking strength and power to serve execution, with caffeine supplementation showing context-dependent ergogenic effects. These findings indicate a need to revise kinetic-chain models for overhead sports and call for strength-and-conditioning programs tailored to serve-specific demands. Future research should adopt longitudinal designs, standardized serve-velocity measurement protocols, and combined strength-power-coordination interventions to clarify causal mechanisms underlying overhead serve performance.